SCIENTIFIC AND PEDAGOGICAL FOUNDATIONS FOR DEVELOPING ECOLOGICAL CULTURE IN FUTURE ENGINEERS (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article examines the scientific and pedagogical foundations for developing ecological culture in future engineers within the context of modern higher education. The relevance of the topic is determined by the increasing need to prepare engineering specialists who are not only technically competent, but also capable of understanding the environmental consequences of professional decisions, technological processes and industrial development. Ecological culture is interpreted as an integrated personal and professional quality that includes environmental knowledge, responsible attitudes toward nature, sustainable thinking, practical ecological skills and readiness to apply environmentally safe solutions in engineering activity. The article emphasizes that the formation of ecological culture among future engineers should be based on an interdisciplinary approach, the integration of ecological content into professional subjects, problem-based learning, project activities, digital technologies and practical tasks connected with real industrial and environmental challenges. Special attention is paid to the role of pedagogical conditions, including the motivation of students, the ecological orientation of the educational environment, cooperation between teachers and industry, and the development of reflective and analytical thinking.